AN EVALUATION OF THE RELATIONSHIP BETWEEN VARIATIONS IN PROVISION OF INFRASTRUCTURE AND PAYMENT OF PROPERTY TAX IN IBADAN NORTH-EAST LOCAL GOVERNMENT, NIGERIA - M.T.A, Ajayi; I, Onuigbo; S.I, Shuaib; A, Anuar; Z.S, Zafirah (Journal of Technology Management and Business, 2016)
The provision of Infrastructural facilities is the reponsibilty of any governemnt within any jurisdiction. The use of property tax to finance the provisions of infrastructure has been globally accepted. However, the problem is that where there is no known form of property taxation to apply, residents cannot determine the benefit derivable from the infrastructure provided. The research methodology therefore adopted System random sampling in Ibadan North East Local Government to examine the 0.0035% of the resident population. Thus the occupier of the residential property within location formed the sample frame. The result presented in Tabular form indicated that while about 58.6% of the population reside in areas with low infrastructure , the existing form of property taxation has created social injustice since similar amount is being paid across the locations inrespective of the level of infrastructure provided. The use of Improvement of land was therefore recommended as the basis for determining property tax. Keywords: Property tax, Local Government, taxation, Infrastructure, System random sampling.